The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.scitotenv.2017.04.097
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and genetic diversity of Cryptosporidium and Giardia in urban wastewater treatment plants in north-eastern Spain

Abstract: This study was designed to investigate the presence and removal efficiency of Cryptosporidium and Giardia in wastewater treatment plants at the 20 most populated towns in Aragón (north-eastern Spain). Samples of influent and effluent wastewater and dewatered sewage sludge were collected seasonally from 23 plants and processed according to USEPA Method 1623. All samples from raw and treated wastewater tested positive for Giardia, at an average concentration of 3247±2039cysts/l and 50±28cysts/l, respectively. Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 63 publications
2
21
0
1
Order By: Relevance
“…The results obtained in our study suggest that Cryptosporidium sp. 1 may correspond to one unnamed Cryptosporidium genotype isolated from an environmental sample in Aragon (north-eastern Spain) and another unnamed genotype isolated from a storm event water sample from New York [82,83]. It was not possible to identify to the species level Cryptosporidium sp.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in our study suggest that Cryptosporidium sp. 1 may correspond to one unnamed Cryptosporidium genotype isolated from an environmental sample in Aragon (north-eastern Spain) and another unnamed genotype isolated from a storm event water sample from New York [82,83]. It was not possible to identify to the species level Cryptosporidium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Australia (King et al 2015a;Zahedi et al 2018), Brazil andPeru (Ulloa-Stanojlović et al 2016;Martins et al 2019), China (Feng et al 2009;Li et al 2012;Huang et al 2017), Japan (Hashimoto et al 2006;Hirata and Hashimoto 2006), Switzerland and Germany (Ward et al 2002), the USA (Xiao et al 2001;Zhou et al 2003) and Tunisia (Ben Ayed et al 2012) (Table 2). While in Europe, a number of studies have reported that C. parvum is the dominant species in wastewater (Hänninen et al 2005;Spanakos et al 2015;Imre et al 2017;Ramo et al 2017). In other countries such as China, Iran, Tunisia and the USA, livestock-associated species such as C. andersoni and C. xiaoi dominate in wastewater samples (Xiao et al 2001;Liu et al 2011;Ben Ayed et al 2012;Hatam-Nahavandi et al 2016;Ma et al 2019) (Table 2).…”
Section: Occurrence Of Protozoans In Wastewatermentioning
confidence: 96%
“…Giardia duodenalis is a protozoan parasite that commonly causes waterborne gastrointestinal illness in humans, with outbreaks across the world (Efstratiou et al, 2017). Giardia cysts are often found in wastewater and biosolid samples at high concentrations, and remains an important waterborne pathogen (King et al, 2016;Ramo et al, 2017a;Ramo et al, 2017b;Rhodes et al, 2015). Since the cyst is the only stable life stage in the environment, viable G. duodenalis cysts are required to study this pathogen in environmental matrices.…”
Section: Introductionmentioning
confidence: 99%